2021
DOI: 10.1016/j.toxrep.2021.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic toxicity of ethanol leaf extract of Syzygium guineense on the biochemical parameters and histopathology of liver and kidney in the rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…However, these alterations in the microscopic structures of the placenta were not statistically significant. Similarly, in another study, there were no significant histological alterations observed in the liver and kidney of rats treated with S. guineense extract [ 18 ]. The decidua basalis is found at the base of the placenta and it contains newly formed vasculatures.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, these alterations in the microscopic structures of the placenta were not statistically significant. Similarly, in another study, there were no significant histological alterations observed in the liver and kidney of rats treated with S. guineense extract [ 18 ]. The decidua basalis is found at the base of the placenta and it contains newly formed vasculatures.…”
Section: Discussionmentioning
confidence: 75%
“…The test plant was verified by a taxonomist in the National Herbarium of Ethiopia with a voucher sample (MS 001) deposited for later remark. Regarding the extraction procedure, we followed the methods of Abebe et al [ 18 ]. Briefly, the leaves of the test plant were cleaned, shade dried, broken into pieces by hand, and roughly ground by an electric mill.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies suggest that flavonoids could reduce fat absorption, boost energy use, and inhibit adipogenesis [ 37 , 38 ]. Similarly, tannins can harm the gastrointestinal mucosa and reduce food intake [ 39 , 40 ]. In addition, the essential oil of O. lamiifolium contains a significant amount of linalool and this compound is known to inhibit lipid accumulation by down-regulating adipocyte differentiation [ 41 ], which could be another potential reason for the reduced weight gain in our rats who received high doses of O. lamiifolium leaf extracts.…”
Section: Discussionmentioning
confidence: 99%
“…A 3 mm tissue sample from the liver, kidney, and brain was taken and preserved in 10% formalin for a purpose of fixation. For the routine tissue processing steps: dehydration, clearing, embedding, mounting, and staining, we followed the methods discussed by Abebe et al [ 15 ].…”
Section: Methodsmentioning
confidence: 99%